Rumble and crash : crises of capitalism in contemporary film - Sweedler, Milo, 1963- (State University of New York Press, 2019)
Analyzes six films as allegories of capitalism's precarious state in the early twenty-first century.
Keywords: Motion pictures -- History -- 21st century.; Capitalism in motion pictures.; Politics in motion pictures.; Cinéma -- Histoire -- 21e siècle.; Capitalisme au cinéma.; Politique au cinéma.; PERFORMING ARTS -- Reference.; Capitalism in motion pictures; Motion pictures; Politics in motion pictures; 2000-2099; History